ANALISIS SISTEM PENILAIAN PERSEDIAAN BARANG DAGANG (Studi Cenningrara Store di Kecamatan Poleang) - Samsiar, Samsiar; Sabarudin, Sabarudin; Bustang, Bustang (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the inventory accounting system implemented by Cenningrara Store. With a qualitative approach, this study explores information about the effectiveness of the existing system. The results of the study indicate that Cenningrara Store uses a manual-based perpetual recording system that allows the company to find out the amount of physical inventory. The assessment method applied is FIFO (First In First Out), where the first goods entered will be sold first. This study also compares two inventory recording methods, namely FIFO and the weighted average method. This analysis reveals that the accounting system implemented has been running effectively, although there are still several aspects that need to be improved, especially in terms of supervision and evaluation to avoid recording errors. This study is expected to contribute to the development of accounting systems in trading companies, as well as being a reference for further research in the field of inventory accounting